2004
DOI: 10.1007/s00425-004-1272-z
|View full text |Cite
|
Sign up to set email alerts
|

Light conditions influence specific defence responses in incompatible plant?pathogen interactions: uncoupling systemic resistance from salicylic acid and PR-1 accumulation

Abstract: In incompatible plant-pathogen interactions, disease resistance is generated by rapid activation of a multitude of plant defence reactions. Little is known about the dependency of these resistance responses on external factors. The plasticity of plant defence mechanisms in terms of light conditions is studied here. Interaction of Arabidopsis thaliana (L.) Heynh. with an avirulent strain of Pseudomonas syringae pv. maculicola in the dark resulted in increased apoplastic bacterial growth and therefore reduced lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
221
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(237 citation statements)
references
References 60 publications
(71 reference statements)
13
221
0
2
Order By: Relevance
“…Our data suggest that 1 O 2 production prevails over FR production and hence 1 O 2 appears as the most relevant ROS with respect to the execution of cell death in leaf tissues. An example of ROSdependent plant cell death is also the hypersensitive response (Torres et al, 2006) during which light seems to be required both to initiate a cell death program, early on in the infection, as well as at later stages of cell death execution (Zeier et al, 2004;Liu et al, 2007). Interestingly, 1 O 2 HOTE markers significantly increased in Arabidopsis leaves challenged with the avirulent strain DC3000 of Pseudomonas syringae (Grun et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that 1 O 2 production prevails over FR production and hence 1 O 2 appears as the most relevant ROS with respect to the execution of cell death in leaf tissues. An example of ROSdependent plant cell death is also the hypersensitive response (Torres et al, 2006) during which light seems to be required both to initiate a cell death program, early on in the infection, as well as at later stages of cell death execution (Zeier et al, 2004;Liu et al, 2007). Interestingly, 1 O 2 HOTE markers significantly increased in Arabidopsis leaves challenged with the avirulent strain DC3000 of Pseudomonas syringae (Grun et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Light is the major external factor influencing plant growth and development, and an appropriate light environment is also required for the establishment of a complete set of resistance responses in several plant-pathogen interactions (Roberts and Paul, 2006). In tobacco (Nicotiana tabacum), rice (Oryza sativa), and Arabidopsis (Arabidopsis thaliana), HR-associated programmed cell death triggered by bacterial and viral pathogens is light dependent (Lozano and Sequeira, 1970;Guo et al, 1993;Genoud et al, 2002;Zeier et al, 2004;Chandra-Shekara et al, 2006). Similarly, the constitutive cell death phenotype of Arabidopsis acd11 and lsd1 mutants is only evident when light of a certain quantity or duration is present (Brodersen et al, 2002;Mateo et al, 2004).…”
mentioning
confidence: 99%
“…Deposition of lignin-like polymers in Xanthomonas oryza-treated rice leaves decrease when light is absent during the first hours after inoculation (Guo et al, 1993). Moreover, Arabidopsis plants inoculated in darkness with an avirulent strain of Pseudomonas syringae are not able to substantially accumulate the phenolic metabolite SA and fail to induce expression of the key phenylpropanoid pathway enzyme Phe ammonia lyase (PAL; Zeier et al, 2004). Light is not only required for SA biosynthesis, but also controls SA perception, because treatment of Arabidopsis leaves with exogenous SA in dim light or in the dark results in strongly reduced expression of the SA-induced defense gene PR-1 (Genoud et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Light seems to be required for HR formation at least for some incompatible interactions. 57 Boccara et al, 58 recently showed that after treatment with the elicitor harpin excess excitation energy (EEE) is being formed in chloroplasts leading to overexcited chlorophyll metabolites. They will react with 3 O 2 and form singlet oxygen ( 1 O 2 ).…”
Section: A Role For the Chloroplastmentioning
confidence: 99%